איך אתה מפשט (^ ^ ^ ^ ^ -2 ז ^ 3) ^ - 2 (x ^ 2y ^ -4z ^ 6)?

איך אתה מפשט (^ ^ ^ ^ ^ -2 ז ^ 3) ^ - 2 (x ^ 2y ^ -4z ^ 6)?
Anonim

תשובה:

השתמש בשלושת המאפיינים הבאים:

# (x * y * z * …) ^ a = x ^ a * y ^ a * z ^ a * … #

# (x ^ a) ^ b = x ^ (a * b) #

# x ^ a * x ^ b = x ^ (a + b) #

תשובה היא:

# x ^ 4y ^ 0z ^ 0 #

הסבר:

# (x ^ -1 y ^ -2z ^ 3) ^ - 2 (x ^ 2y ^ -4z ^ 6) # #

  • להשתמש # (x * y * z * …) ^ a = x ^ a * y ^ a * z ^ a * … #

# (x ^ -1) ^ - 2 (y ^ -2) ^ - 2 (z ^ 3) ^ - 2x ^ 2y ^ -4z ^ 6 #

  • להשתמש # (x ^ a) ^ b = x ^ (a * b) #

# ^ (- 1) (- 2) (- 2 * (- 2)) z (3 * (- 2)) x ^ 2y ^ -4z ^ 6 #

# x ^ 2y ^ 4z ^ -6x ^ 2y ^ -4z ^ 6 #

  • להשתמש # x ^ a * x ^ b = x ^ (a + b) #

# x ^ (2 + 2) y ^ (4 + (- 4)) z ^ (- 6 + 6) #

# x ^ 4y ^ 0z ^ 0 #

הערה: לא אומר את זה # y ^ 0 = 1 # ו # z ^ 0 = 1 # כי זה לא נכון # y = 0 # ו # z = 0 #

אם אתה רוצה אתה יכול להשתמש # x ^ -a = 1 / x ^ a # אבל זה קל יותר בלעדיו.